"ENVIRONMENTAL PROBLEMS IN URBAN SLUMS" (WITH REFERENCE TO KHANDWA CITY): ’’शहरी गंदी बस्तियों में पर्यावरण संबंधी समस्याएँ’’ (खण्डवा शहर के संदर्भ में) - Gaikwad, Sushila (International Journal of Research -GRANTHAALAYAH, 2015)
Presently, the environment and environment that surrounds us is called Pariran. The balance of all the components in the environment is necessary in a certain proportion, but due to man’s desire for rapid development and tampering with nature, this balance is slowly ending. The ever-increasing population on Earth is becoming a major cause of concern in the world today, as population growth has affected almost all countries in some way and has hindered their progress. The pressure of population is not much in the developed countries, but the situation is very pathetic in the developing and underdeveloped countries. This rate of population growth is worrying, because despite the continuous growth, most of our population is living low standard of living. Notwithstanding the unprecedented increase in food production, nutrition is not available to all. The situation is getting pathetic. Resources are running out, there is energy crisis, shortage of drinking water and environment is polluted. Due to increasing population, deforestation of forests, unnecessary exploitation of ground water, proliferation of residential colonies, lack of energy, etc. have created problems. वर्तमान में हम जिस वातावरण एवं परिवेष द्वारा चारों ओर से घिरे है उसे पर्यारण कहते है। पर्यावरण में सभी घटकों का निष्चित अनुपात में संतुलन आवष्यक है, किन्तु मनुष्य की तीव्र विकास की अभिलाषा एवं प्रकृति के साथ छेड़छाड़ के कारण यह संतुलन धीरे-धीरे समाप्त हो रहा है। पृथ्वी पर निरंतर बढ़ती जनसंख्या आज विष्व में चिंता का प्रमुख कारण बन रही है, क्योंकि जनसंख्या वृद्धि ने लगभग सभी देषों को किसी न किसी प्रकार से प्रभावित किया है और उनकी प्रगति में बाधाएं उत्पन्न की है। जनसंख्या का दबाव विकसित देषों में तो कुछ अधिक नहीं है, किंतु विकासषील व अविकसित देषों में स्थिति बहुत अधिक दयनीय है। जनसंख्या वृद्धि की यह दर चिंताजनक है, क्योंकि निरंतर विकास के बावजूद भी हमारी अधिकांष जनसंख्या निम्न जीवन स्तर जी रही है। खाद्यान उत्पादन में अपूर्व वृद्धि के बावजूद सभी को पोषक उपलब्ध नहीं है। अधिक स्थिति दयनीय हो रही है। संसाधन समाप्त हो रहे है, ऊर्जा का संकट है, पेयजल की कमी और पर्यावरण प्रदुषित है। बढ़ती जनसंख्या के कारण वनों का विनाष भूमिगत जल का अनावष्यक दोहन, आवासीय काॅलोनियों का प्रसार, ऊर्जा की कमी आदि समस्याएँ उत्पन्न हो गई है।